2012
DOI: 10.1073/pnas.1205870109
|View full text |Cite
|
Sign up to set email alerts
|

Collective mesendoderm migration relies on an intrinsic directionality signal transmitted through cell contacts

Abstract: Collective cell migration is key to morphogenesis, wound healing, or cancer cell migration. However, its cellular bases are just starting to be unraveled. During vertebrate gastrulation, axial mesendoderm migrates in a group, the prechordal plate, from the embryonic organizer to the animal pole. How this collective migration is achieved remains unclear. Previous work has suggested that cells migrate as individuals, with collective movement resulting from the addition of similar individual cell behavior. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(128 citation statements)
references
References 48 publications
(57 reference statements)
9
109
1
1
Order By: Relevance
“…At the onset of gastrulation, internalized lateral mesodermal and endodermal cells initially move anteriorly, and at mid-gastrulation turn their trajectories towards the dorsal midline (Dumortier et al, 2012;. In order to better understand the relationship between the cell body alignment and this movement behavior, we analyzed the trajectories of WT and vangl2 mutant cells.…”
Section: Spatiotemporal Dynamics Of ML Elongation Of Mesodermal Cellsmentioning
confidence: 99%
“…At the onset of gastrulation, internalized lateral mesodermal and endodermal cells initially move anteriorly, and at mid-gastrulation turn their trajectories towards the dorsal midline (Dumortier et al, 2012;. In order to better understand the relationship between the cell body alignment and this movement behavior, we analyzed the trajectories of WT and vangl2 mutant cells.…”
Section: Spatiotemporal Dynamics Of ML Elongation Of Mesodermal Cellsmentioning
confidence: 99%
“…Transplant experiments show that isolated prechordal plate cells are unable to migrate directionally until they make contact with the rest of the collective (Dumortier et al, 2012). Importantly, this work suggested that intrinsic directional information might arise from cell-cell interactions independently of guidance cues (Dumortier et al, 2012). Does contact-dependent polarity also occur in migratory epithelial collectives?…”
Section: Contact Inhibition Of Locomotion: Polarizing the Collectivementioning
confidence: 98%
“…Although the role of CIL in controlling directional migration of the neural crest is well established Theveneau et al, 2010Theveneau et al, , 2013, accumulating evidence suggests that CIL is present in other collective migration systems as well. Recent work has shown that Wnt/PCP-mediated contact-dependent polarity drives collective migration of zebrafish prechordal plate cells (Dumortier et al, 2012) by controlling E-cadherin/Rac-dependent protrusion formation. Transplant experiments show that isolated prechordal plate cells are unable to migrate directionally until they make contact with the rest of the collective (Dumortier et al, 2012).…”
Section: Contact Inhibition Of Locomotion: Polarizing the Collectivementioning
confidence: 99%
See 2 more Smart Citations